Lower bounds for non-convex stochastic optimization - Arjevani, Yossi; Carmon, Yair; Duchi, John C.; Foster, Dylan J.; Srebro, Nathan; Woodworth, Blake (Mathematical programming, 2023)
We lower bound the complexity of finding ϵ -stationary points (with gradient norm at most ϵ ) using stochastic first-order methods. In a well-studied model where algorithms access smooth, potentially non-convex functions through queries to an unbiased stochastic gradient oracle with bounded variance, we prove that (in the worst case) any algorithm requires at least ϵ - 4 queries to find an ϵ -stationary point. The lower bound is tight, and establishes that stochastic gradient descent is minimax optimal in this model. In a more restrictive model where the noisy gradient estimates satisfy a mean-squared smoothness property, we prove a lower bound of ϵ - 3 queries, establishing the optimality of recently proposed variance reduction techniques.